Bits and Pieces Screening Animal Life and Death - O'Brien, Sarah (University of Michigan Press, 2023)
Bits and Pieces: Screening Animal Life and Death gathers pivotal and more mundane moments, dispersed across a predominantly Western history of moving images, in which animals materialize in movies and TV shows, from iconic scenes of cattle slaughter in early Soviet montage to quandaries over hunting trophies in recent home-renovation reality TV series, to animals in Black horror films. Sarah O'Brien carefully views these fragments in dialogue with germinal texts at the intersection of animal studies, film and television studies, and cultural studies. She explores the capacity of moving images to unsettle the ways in which audiences have become habituated to viewing animal life and death on screens, and, more importantly, to understanding these images as more and less connected to the "production for consumption" of animals that is specific to modern industrialization. By looking back at films and TV series in which the places and practices of killing or keeping animals enter, occupy, or slip from the foreground, Bits and Pieces takes seriously the idea that cinema and television have the capacity not only to catch but to challenge and change viewers' regard for animals.